Capturing dynamic phage–pathogen coevolution by clinical surveillance - Yamini Mathur; Caroline M. Boyd; Jeannette E. Farnham; Md Mamun Monir; Mohammad Tarequl Islam; Marzia Sultana; Tahmeed Ahmed; Munirul Alam; Kimberley D. Seed (Nature, 2026)
Abstract Bacteria harness diverse defence systems that protect against phage predation 1 , many of which are encoded on horizontally transmitted mobile genetic elements 2 . In turn, phages evolve counter-defences 3 , driving a dynamic arms race that remains underexplored in human disease contexts. For the diarrhoeal pathogen Vibrio cholerae , a higher burden of its lytic phage ICP1 in patient stool correlates with reduced disease severity 4 . However, direct molecular evidence of lytic phages driving selection of epidemic V. cholerae has not been demonstrated. Here, through clinical surveillance in cholera-endemic Bangladesh, we capture the acquisition of a parasitic anti-phage mobile genetic element, PLE11, that initiated a selective sweep coinciding with the largest cholera outbreak in recent records. PLE11 showed potent anti-phage activity against cocirculating ICP1, explaining its rapid and dominating emergence. We identify PLE11-encoded Rta as the defence responsible and provide evidence that Rta restricts phage tail assembly. Using experimental evolution, we predict phage counteradaptations against PLE11 and document the eventual emergence and selection of clinical ICP1 that achieve a convergent evolutionary outcome. Finally, we discover how PLEs balance their dependence on ICP1 tail proteins for horizontal transmission with the restriction of phage tail assembly by Rta: PLEs construct chimeric tails composed of both mobile genetic element-encoded and phage-encoded proteins to ensure their transmission. Collectively, our findings reveal the molecular basis of the natural selection of a globally important pathogen and its virus in a clinically relevant context.